Mortality in Edentulous Patients: A Registry-Based Cohort Study in Sweden Comparing 8463 Patients Treated with Removable Dentures or Implant-Supported Dental Prostheses - Jan Kowar; Victoria Stenport; Mats Nilsson; Torsten Jemt (International Journal of Dentistry)
Objectives. The purpose of this study was to investigate if edentulism is associated with all-cause mortality. The aims were to analyze the association between age, socioeconomic factors, and mortality in edentulous patients treated with either removable dentures or implant-supported prostheses. Methods. All patients who became edentulous according to the Swedish Social Insurance Agency (SSIA) between 2009 and 2013 (N  = 8463) were analyzed regarding prosthetic treatment, age, gender, and socioeconomic status. The patients were divided into two groups, depending on whether they were treated with dental implants (implant group; IG) or with conventional removable dentures (denture group; DG). Data on mortality for all included individuals were obtained from the Swedish National Cause of Death Register and compared to a reference population. Cumulative survival rates were calculated, and a multivariable regression analysis for the included variables was performed. Results. Between 2009 and 2018, 2192 of the patients (25.9%) were treated with implant-supported dental prostheses (IG) and 6271 patients (74.1%) were treated with removable dentures without support of dental implants (DG). Altogether 2526 patients (30%) died until December 31, 2019, and the overall mortality was significantly higher for the DG compared to the IG during follow-up (p<0.001). Younger edentulous patients (≤59 years) presented a higher mortality than the reference population, while implant patients over 79 years of age demonstrated a lower mortality. The final results from the multivariable logistic analysis showed that lower equalized disposable income (EDI) and the choice of conventional removable dentures are the most important factors for increased patient mortality (p<0.001). Conclusions. Edentulous patients have an overall higher mortality compared to a reference population. Low socioeconomic status increases all-cause mortality. Individuals treated with dental implants show statistically significant lower 10-year mortality compared to patients treated with conventional removable dentures, regardless of socioeconomic status.